2023
DOI: 10.1111/brv.12993
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific behavioural interference and range dynamics: current insights and future directions

Abstract: Novel biotic interactions in shifting communities play a key role in determining the ability of species' ranges to track suitable habitat. To date, the impact of biotic interactions on range dynamics have predominantly been studied in the context of interactions between different trophic levels or, to a lesser extent, exploitative competition between species of the same trophic level. Yet, both theory and a growing number of empirical studies show that interspecific behavioural interference, such as interspeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 171 publications
0
2
0
Order By: Relevance
“…Other negative species interactions have often been assumed to have effects similar to exploitative competition, but theoretical and empirical research has shown that not to be the case. Direct interactions, such as aggressive and reproductive interference, can shape species distributions in ways that would not be predicted by niche theory (Grether et al, 2017;Grether & Okamoto, 2022;Kishi & Nakazawa, 2013;Patterson & Drury, 2023). Interspecific interference does not consistently favour species with higher intrinsic growth rates and can cause Allee effects that prevent species from persisting at low densities in environments that could support much higher densities (Case et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Other negative species interactions have often been assumed to have effects similar to exploitative competition, but theoretical and empirical research has shown that not to be the case. Direct interactions, such as aggressive and reproductive interference, can shape species distributions in ways that would not be predicted by niche theory (Grether et al, 2017;Grether & Okamoto, 2022;Kishi & Nakazawa, 2013;Patterson & Drury, 2023). Interspecific interference does not consistently favour species with higher intrinsic growth rates and can cause Allee effects that prevent species from persisting at low densities in environments that could support much higher densities (Case et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although interference competition has often been inferred to be the cause of species replacements along elevational and habitat gradients (Heller 1971;Cody and Walter 1976;Schoener 1983;Robinson and Terborgh 1995;Jankowski et al 2010Jankowski et al , 2012Freeman et al 2019;Patterson and Drury 2023), the types of manipulative field experiments required to distinguish competitive displacement from ACD are rarely done. Most such experiments that have been published implicate competitive displacement (e.g., Reed 1982;Garcia 1983;Ebersole 1985;Robertson and Gaines 1986;Ziv et al 1993;Robertson 1996;Martin and Martin 2001;Stewart et al 2002;Harmon et al 2007;Pasch et al 2013;Edgehouse et al 2014;Eurich et al 2018;Martin and Ghalambor 2023), but this could reflect a long-standing bias against publishing negative results.…”
Section: Introductionmentioning
confidence: 99%